2009
DOI: 10.1074/jbc.m807546200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Protein Kinase D2 as a Pivotal Regulator of Endothelial Cell Proliferation, Migration, and Angiogenesis

Abstract: Angiogenesis, the formation of new blood vessels, plays a crucial role in normal physiological processes and in various pathological conditions. In the present study, we have investigated the physiological function of a newly described serine/threonine protein kinase D2 (PKD2) in aspects of endothelial cell biology involved in angiogenesis. We found that PKD2 was expressed in primary human endothelial cells from different tissues and was a critical PKD isoform mediating the phosphorylation of PKD substrates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 33 publications
8
52
0
3
Order By: Relevance
“…This suggests that PKD2 may be required for nonVEGF-mediated angiogenic mechanisms. In support of this hypothesis they found that PKD2 was also required for fibroblast growth factor receptor expression (33). Further work using PKD isoform specific mutants or endothelial specific knockouts will be required to further clarify the roles of the PKD isoforms in endothelial function.…”
Section: Pkd Function In Endothelial Cellssupporting
confidence: 53%
See 1 more Smart Citation
“…This suggests that PKD2 may be required for nonVEGF-mediated angiogenic mechanisms. In support of this hypothesis they found that PKD2 was also required for fibroblast growth factor receptor expression (33). Further work using PKD isoform specific mutants or endothelial specific knockouts will be required to further clarify the roles of the PKD isoforms in endothelial function.…”
Section: Pkd Function In Endothelial Cellssupporting
confidence: 53%
“…PKD2 seems to be more abundantly expressed in HUVECs compared with PKD1, as judged by an antibody that recognized both isoforms, and knockdown of PKD2 appears to have a greater effect on HSP27 phosphorylation (9). In addition, Hao et al showed that only PKD2 knockdown was able to inhibit endothelial migration, proliferation and tube formation stimulated by serum (33). This suggests that PKD2 may be required for nonVEGF-mediated angiogenic mechanisms.…”
Section: Pkd Function In Endothelial Cellsmentioning
confidence: 93%
“…These findings suggest a functional differentia among PKD isoforms. We have reported that PKD1 regulates the production of proinflammatory cytokines by vascular endothelial growth factor (VEGF) in endothelial cells (29) and that PKD2 is pivotal for angiogenesis (30). We also found that both PKD2 and PKD3 were novel growth regulators in triple-negative breast cancer cells (31).…”
mentioning
confidence: 84%
“…1B). By using a phospho-Ser/Thr PKD substrate antibody that specifically recognizes the PKD consensus motif LXRXX(S/T) and PKD-mediated protein phosphorylation (30,42), we found that the PKD-dependent protein phosphorylation in 16HBE14oϪ cells was markedly suppressed by the selective PKD inhibitor kb-NB142-70 (Fig. 1C, top panel).…”
Section: Inhibition Of Pkd Activity or Silencing Of Pkd Increase Teermentioning
confidence: 97%
“…Human umbilical vein endothelial cells (HUVECs, Lonza Walkersville) were cultured in endothelial growth medium-2 (EGM-2; cc-3162, Lonza Walkersville) referred to as growth factor containing medium as described previously 24 and used at early passages 1-6. When indicated, HUVEC cultures were switched to EBM-2 medium (Lonza Walkersville) referred to as a growth factor-depleted medium that was supplemented with either 0.5% FCS or ITS (insulin 10 g/mL, transferrin 6.7 ng/mL, selenium 5.5 g/mL).…”
Section: Cellsmentioning
confidence: 99%